Evaluation of the productivity and plant health of pruned coffee intercropped with annual crops - Oliveira, Marcela Cristina Silva de; Santini, Paula Tristão; Rezende, Ana Paula da Silva; Funchal, Miguel; Teruel, Tiago; Mendonça, José Marcos Angélico de (Revista Agrogeoambiental, 2020)
Alley intercipiente with annual crops is a usual practice in coffee cultivation, especially in periods of renewal of the crop by pruning. Its purpose is to make better use of the area, decrease costs of implantation and renovation, mainly in coffee plantations with open lines, through the production of subsistence food with generation of additional and immediate income of the producer. Therefore, the objective of the present study was to evaluate the productivity and plant health of pruned coffee crop in consortium with annual crops in different spacings. The experiment was carried out at the Instituto Federal de Educação, Ciência e Tecnologia do Sul de Minas Gerais – Campus Muzambinho, in the 2016/17 and 2017/2018 crop years, in a coffee plant of Catuaí Vermelho cultivar 144, 12 years old, pruned in 2014. Three intercrops (corn, chia and beans) in two spacings (30.0cm and 60.0cm) plus two additional treatments without intercropping (slashing or applying herbicide) were implanted in the soil. In the crop year 2016/17, a delay in the fruit maturation was observed in the treatment with intercropping spaced at 30.0cm, when compared to the same crops at 60.0cm spacing. The maturation of the fruits in the 2017/18 crop year was delayed in the treatments of consorts spaced at 60.0cm, when compared with the additional treatment. There was an expressive increase of cercosporiosis with cropping culture spacing 60.0cm. It was also observed that the average yield of coffee in the 2016/17 and 2017/18 crop years was affected by the interplant cultures implanted in the spacing of 30.0cm. In general, regardless of the spacings, intercropping negatively influenced the productivity of coffee in both 2016/17 and 2017/2018 crop years.